BLAST PLASMACYTOIN DENDRITIC CELL NEOPLASIA (CLINICAL CASE) - Марина Владимировна Косинова; Михаил Дмитриевич Неверов; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Кира Борисовна Мозес; Яэль Центер (Медицина в Кузбассе, 2022)
Blast plasma dendritic cell neoplasia is a rare, clinically aggressive type of tumor characterized by clonal proliferation of plasmacytoid dendritic cell precursors with involvement in the pathological process, mainly of the skin and bone marrow, followed by leukemization of the process. The exact frequency of occurrence of the process is unknown. The appearance of the tumor is not associated with any racial or ethnic group. The ratio of men and women is 3.3 : 1. Most patients are over 60 years old. The average age is 61-67 years, but this neoplasm can occur at any age, including in children. This article describes a clinical case of blast plasma dendritic cell neoplasia with a fatal outcome.